La ferme sans le tracteur : les illustrations pour enfants d’Arkadiï Plastov - Juliette Milbach (Strenae)
Arkady Plastov's (1893-1972) children's illustrations had two main periods: the late 1920s and the turn of the 1940s-1950s. During this second period, Plastov produced three works (L’année au kolkhoze; Les animaux domestiques; and À propos des animaux domestiques) in the tradition of Russian and Soviet animal artists. These illustrations are linked to the context, from the years of scarcity to the end of Stalinism, and to their author, who was a painter before becoming an illustrator. They show a personal interpretation of rural life in the Soviet Union aimed at a younger generation.